Improvement of polyphenolic content and antioxidant activity of Syrian myrtle berries (Myrtus communis L.) hydro-alcoholic extracts using flavoring additives - Zam, Wissam; Ali, Ali; Ibrahim, Walaa (Progress in Nutrition, 2017)
Myrtle berries extracts were prepared using hydro-alcoholic solvent at different concentrations of alcohol ranging from 50 to 80% (v/v). Cloves and cinnamon were used as flavoring additives in different mixtures (myrtle berries; myrtle berries and cinnamon; myrtle berries and cloves; myrtle berries, cinnamon, and cloves) in order to enhance the phenolic content and the antioxidant activity of the liqueur. Total phenolic content was assessed by Folin-Ciocalteau assay, and DPPH (2,2-diphenyl-1-picrylhydrazyl) assay was used to evaluate the total antioxidant activity. The highest content of polyphenols reached 7.82 g/100 g DW after 60 days of myrtle berries and cloves mixture maceration in 50% hydro-alcoholic solution, and the antioxidant efficacy of this mixture was the highest with 80.02% of DPPH scavenging activity. In conclusion, adding cloves to the myrtle berries liqueur will provide the best yield of extracted bioactive compounds with the best antioxidant activity which will affect positively the vital properties for these liqueurs.